Analysis of Employee Recruitment At PT BTPN Syariah Tangerang Selatan Branch - Jeni Andriani (ADPEBI, 2022)
This study aims to analyze employee recruitment at PT BTPN Syariah South Tangerang Branch. Recruitment analysis consists of processes, sources, stages, constraints and systems. This research method is qualitative research, with collection techniques using documentation, observation, and interviews. The results of the research are that this recruitment process uses 2 (two) methods, namely internal methods and external methods, recruitment sources use a special program namely the Amazed Program, the recruitment stage begins by checking the portfolio or files of prospective candidates such as background, education, and work experience, recruitment constraints there are still traditional elements, and the recruitment system uses 2 (two) systems, namely the skills system and the increased system.